Efficiency and duality for multiobjective fractional variational problems with (ρ,b) - quasiinvexity - Mititelu Ştefan; Stancu-Minasian I.M. (Yugoslav Journal of Operations Research, 2009)
The necessary conditions for (normal) efficient solutions to a class of multi-objective fractional variational problems (MFP) with nonlinear equality and inequality constraints are established using a parametric approach to relate efficient solutions of a fractional problem and a non-fractional problem. Based on these normal efficiency criteria a Mond-Weir type dual is formulated and appropriate duality theorems are proved assuming (ρ,b) - quasi-invexity of the functions involved.